HISTORY AND DEVELOPMENT OF AUTOMATED CONTROL SYSTEMS - Khidirova , Nailya (Techscience uz - Topical Issues of Technical Sciences, 2024)
This article examines the history and development of automated control systems from the first mechanical devices to modern digital systems. The evolution of the main technologies and concepts that influenced the integration of information technologies, the development of network solutions, and the development and improvement of automated control systems was studied. The stages of development of automated control systems are analyzed: from primary automation systems in industry to modern integrated control systems in various industries. The article also discusses the problems and problems associated with the safety and reliability of automated control systems and discusses ways to overcome them.